APPLICATION OF GEOELECTRIC METHOD FOR AQUIFER IDENTIFICATION AT LOWER SLOPES OF VOLCANO IN SMALL VOLCANIC ISLAND OF TERNATE - Fikry, Adam
Ternate Island is a small island located in eastern Indonesia which has a complex geology. The existence of the Gamalama volcano makes the morphology of the island of Ternate have steep and sloping areas from the top of the mountain to the coast. Despite the small size of the island and the presence of volcano, there are settlements that tend to be located on the gently sloping coastal areas. This study aims to identify aquifers in the lower volcanic slopes of Ternate Island by applying the geoelectric method. The resistivity measurement was carried out with the Wenner and Schlumberger configurations according to the conditions of the measurement area. There are nine measurement lines around the slopes of the volcano. From the measured data, 2D resistivity model was made using Res2DInv software. Based on 2D resistivity modeling, the range of resistivity values on the SKB line is 12.6 - 667 ?m, Facei 50.8 - 871 ?m, Salahudin 20.1 - 4441 ?m, Kalumata 11.7 - 6134 ?m, Brimob 54.2 - 1344 ?m, Jambula 136 - 1437 ?m, BPCB 60.1 - 493 ?m, Ake Rica 0.561 - 114 ?m and Loto 0.470 - 54.2 ?m. Of all the lines studied, there are two areas where the aquifers are suspected to be filled with salt water, namely Ake Rica and Loto. In the 2D resistivity model of the two lines, it can be seen that there is a low resistivity distribution contour. Interpretation is done by utilizing geophysical data, geological information and conductivity data of water samples.